A microfluidic fluidized bed to capture, amplify and detect bacteria from raw samples - Alexandre, Lucile; Pereiro, Iago; Bendali, Amel; Tabnaoui, Sanae; Srbova, Jana; Bilkova, Zuzana; Deegan, Shane; Joshi, Lokesh; Viovy, Jean-Louis; Malaquin, Laurent; Dupuy, Bruno; Descroix, Stéphanie (Methods in cell biology, 2018)
Bacterial contamination and subsequent infections are a major threat to human health. An early detection in the food chain, clinics or the environment, is key to limit this threat. We present a new concept to develop low-cost hand-held devices for the ultra-sensitive and specific detection of bacteria in a one-step process of 2-8h, directly from complex raw samples. This approach is based on a novel microfluidic magnetic fluidized bed. It reaches a 4CFU (colony forming unit) sensitivity with high quantification accuracy in a large dynamic range of 100-107CFU/mL. The versatility of the approach was demonstrated with the detection of different bacteria strains, among which Salmonella Typhimurium and E. coli O157:H15. Additionally, the method is sensitive to infectious bacteria only, a criterion requested by main applications and currently requiring additional culture steps of one to several days.
Keywords: Magnetic beads; Microfluidics; Salmonella typhimurium; Capture; Amplification; Anti-Bacterial Agents; počítačové zpracování obrazu; antibakteriální látky; Bacteria; Detection; Fluidized bed; Image Processing, Computer-Assisted; mikrofluidika